Evaluation the activity of Neuropeptide Y (NPY), Glucagon like peptide-1 and Ghrelin in controlling appetite in obesity in Erbil City - Sawen Tahseen Taha; Leweza Belal Abbas (Zanco Journal of Pure and Applied Sciences, 2023)
The epidemic of obesity is at previously unheard-of heights. In 2016, it was predicted that 39% and 13% of individuals worldwide were overweight or obese, respectively. Obesity, which is defined as an imbalance between energy intake and expenditure, results from multiple interactions between genetic, environmental, psychological, behavioral, and nutritional variables, making it a difficult condition to study and treat. The present study aimed to approach the understanding of appetite, bodyweight regulation and the causes of obesity through studying gastrointestinal hormones such as (NPY, GLP-1, and ghrelin) hormones and their impact on controlling appetite in obesity. This comparative study included (152) participants (Obese and non-Obese) in the age range (30-66 years), both males and females who visited (The surgical specialty hospital cardiac center, Hawler teaching hospital, and Erbil’s court). A self-administered questionnaire was used for data collection. Fasting serum metabolic parameters and hormones were measured included (S.NPY, S.GLP-1, S.Ghrelin) and (S.Total Cholesterol, S.Triglycerides, S.HDL, S.LDL, and S.VLDL). According to the BMI of participants, there was a significant association (P < 0.001) between NPY, GLP-1 hormones and BMI, and a significant (p = 0.033) association between Ghrelin and BMI. The present study concluded that serum NPY, GLP-1 and Ghrelin hormones significantly impacted controlling appetite in obesity, would be a useful and important marker to evaluation for obesity. And a strong relationship between these hormones and obesity.